Optimizing Airport Land Side Operations: Check-In, Passengers’ Migration, and Security Control Processes - Ludovica Adacher; Marta Flamini (Journal of Advanced Transportation)
This paper deals with the optimization of the Check-in, passenger migration, and Security Control processes in an airport land side terminal. Given the layout of the terminal, the passengers’ flow, and the scheduled flights in a given time interval, the number and the position of Check-in counters and Security Control gates to be opened are output. The objective function is the minimization of the costs to activate the Check-in counters and the Security Control gates plus the costs that measure the passengers’ discomfort. The stochastic passengers’ behaviour and their preferences are simulated by a discrete event model, while the managing costs and the passengers’ discomfort are optimized by the Surrogate Method. Capodichino Airport, located in Naples (IT), has been considered for the test phase. Results show the effectiveness and efficiency of the solutions of the Surrogate Method compared with the performances of other algorithms.